Building Academic Integrity and Capacity in Digital Assessment in Higher Education - Lorraine Bennett; Ali Abusalem (Athens Institute for Education and Research, 2024)
The rapid spread of the COVID-19 pandemic in the first half of 2020 disrupted and changed higher education across the world, and into the future. Campuses were shut down, almost overnight. International and State borders were closed and business models that relied heavily on high-paying international students collapsed. University leaders and academics were forced to find new ways of attracting, engaging with, and retaining students. This paper describes a project that was undertaken in Australia in 2021 which investigated the implications of, and scope for online assessment in this 'new virtual world' of learning and teaching in higher education. After extensive research and consultation, the project developed a Digital Assessment Framework dubbed DASH C21, which stands for Digital Assessment Stretching Horizons for the 21st Century. The Framework is based on a set of underpinning principles and values; the Inputs. The Inputs feed into four Dimensions. These Dimensions are Practices and Pedagogies, Strategies, Emerging Technologies and Stretching Horizons. The Outputs are a series of authentic, innovative, experiential and forward looking, digital assessments, reinforced by academic integrity values. This paper will be of particular interest to higher education senior managers, academics, learning and teaching specialists, staff professional developers and curriculum designers.